Transposition in Shigella dysenteriae: isolation and analysis of IS911, a new member of the IS3 group of insertion sequences. - Prère, M F (1990)
Twenty-nine clear-plaque mutants of bacteriophage lambda were isolated from a Shigella dysenteriae lysogen. Three were associated with insertions in the cI gene: two were due to insertion of IS600, and the third resulted from insertion of a new element, IS911. IS911 is 1,250 base pairs (bp) long, carries 27-bp imperfect terminal inverted repeats, and generates 3-bp duplications of the target DNA on insertion. It was found in various copy numbers in all four species of Shigella tested and in Escherichia coli K-12 but not in E. coli W. Analysis of IS911-mediated cointegrate molecules indicated that the majority were generated without duplication of IS911. They appeared to result from direct insertion via one end of the element and the neighboring region of DNA, which resembles a terminal inverted repeat of IS911. Nucleotide sequence analysis revealed that IS911 carries two consecutive open reading frames which code for potential proteins showing similarities to those of the IS3 group of elements.